Penerapan Algoritma C4.5 Dalam Klasifikasi Prestasi Atlet: Studi Kasus Pada Daftar Nama Penerima Penghargaan Tahun 2023 - Andi Diah Kuswanto; Hotman Nicolas Badjo; Septian Kharist; Muhammad Zayyid Mubarok; Riski Saputra; Rivaldi Muhamad Fitroh (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
This study aims to apply the C4.5 algorithm in classifying athlete performance based on the 2023 award recipient list. The C4.5 algorithm was chosen for its ability to construct decision trees that can identify patterns and characteristics distinguishing high-performing athletes. The data used in this study includes various attributes such as gender, age, sport, number of medals, and level of competition participation. The results show that the C4.5 algorithm can classify athletes with high accuracy. The resulting decision tree provides valuable insights into the key factors contributing to athlete performance. The implementation of this algorithm is expected to assist sports organizations in more effectively identifying and developing potential talents.